Chemical treatment of monocrystalline cadmium telluride and Cd₁₋xMnxTe solid solutions by Н₂О₂–НІ–citric acid etchant compositions - Denysyuk, R.O.; Tomashik, V.M.; Tomashik, Z.F.; Chernyuk, O.S.; Grytsiv, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Dissolution of CdTe and Cd₁₋xMnxTe single crystals in aqueous solutions of
Н₂О₂–НІ–citric acid system has been studied. The surfaces of equal etching rates were
constructed and the limiting stages of the dissolution process were ascertained. Also
determined were the concentration limits for the solutions that can be used for chemical
polishing the above-mentioned semiconductor materials.